Education Burnout and Engagement in Occupational Therapy Undergraduate Students and Its Associated Factors - Morales-Rodríguez, Francisco Manuel; Pérez-Mármol, José M.; Brown, Ted (Frontiers in Psychology, 2019)
Abstract Introduction: Burnout syndrome has been characterized as a process of chronic responses to occupational stress in certain employee groups. However, this phenomenon has also been reported in other participant groups including university students. The Maslach Burnout Inventory-Student Survey (MBI-SS), composed of the Exhaustion, Cynicism and Efficacy subscales, was used to evaluate burnout in this sample group while the Utrecht Work Engagement Scale (UWES) was used to gather data related to engagement, a positive psychology construct composed of the three factors, namely vigor, dedication and absorption. To date, no studies considered these factors in relation to occupational therapy students. This begs the question, is there a relationship between occupational therapy students’ self-reported levels of burnout and engagement? Objectives: The study objectives are to, 1) ascertain the self-reported levels of burnout and engagement in a sample of Australian Occupational undergraduate therapy students, and 2) analyze the sociodemographic, occupational and academic characteristic associated with these levels. Methods: Participants were 225 Australian undergraduate occupational therapy students from Monash University completed the MBI-SS and the UWES for students. Descriptive, bivariate and multiple linear regression analyses were performed. Results: Regarding MBI-SS burnout dimensions, exhaustion was associated with age, year level of enrolment and hours of direct time spent working on occupational therapy studies, explaining 15% of its variance. Cynicism and efficacy were associated with age, year level of enrolment and hours of indirect time, accounting for 16% of its variance. For the UWES engagement dimensions, year level of enrolment and hours of indirect time spent working on occupational therapy studies were significant predictors of vigor, explaining 26% its variance while age, gender, hours of indirect time spent working on occupational therapy studies, and hours spend per week engaged in self-care activities accounted for 21% of the variance of dedication. Finally, age, year level of enrolment, and hours of indirect time spent working on occupational therapy studies explained 26% of the variance of absorption. Conclusions: The results indicate that a number of demographic and academic study variables are significantly associated with burnout syndrome and education engagement reported by undergraduate occupational therapy students.